Perancangan Video Cara Mencuci Tangan Bagi anak Tunarungu - Muclis Darma Prasetyo (LPPM STIKI Malang, 2019)
The behavior of a healthy life is one of the important things for each person a small child was no exception. The introduction of health early on in these habits need to be applied to adults, there are many ways of maintaining health one is hand washing. Why should hand wash because the mainstream media is in the hands of the cause of the influx of germs in the body of every person especially in children. Design of video media how to wash your hands for deaf children as alternative media to enhance insight knowledge of deaf children SLB B Naqvi. Instruction in maintaining health in particular keep clean hands only delivered orally. The design of Informative videos how to wash hands in deaf children can make more happy and understand the importance of maintaining healthy hands. This media is designed based Video using After effects, Vegas Pro14, and Adobe Illustrator, has a size of 1920 x 1080 pixels pixels. The result of the design resulted in a mainstream media, namely hand washing way Informative video to enhance the independence of deaf children and supporting multiple media like a CD Case, Posters, t-shirts, bumper stickers, key chains, pins, and Tote Bag. This media can be applied in school SLB B Naqvi as the companion material, media can be run through the Mobile screen or projector, as well as the display in place of the sink so that the learners are more interested and diligent in keeping kesahatan hand with hand washing.